Relationship between online game addiction and sleep quality in students - Silvia, Febiola; Ifdil, Ifdil; Amalianita, Berru; Muryono, Sigit (Konselor, 2022)
This study aims to analyze and evaluate the relationship between online game addiction and sleep quality in students at senior high school 1 Lubuk Sikaping.. The method used in this study is a quantitative method with descriptive and correlational research types. The sample in this study amounted to 30 students of class XII at senior high school  1 Lubuk Sikaping. The data were analyzed using descriptive analysis techniques and Pearson product moment correlation analysis with the help of the JASP version 16.3 program. The results of the study revealed that online game addiction of students at senior high school 1 Lubuk Sikaping is generally in the high category, and sleep quality in students at senior high school 1 Lubuk Sikaping is generally in the low category, and there is a significant relationship between online game addiction and sleep quality at students at senior high school 1 Lubuk Sikaping